2011
DOI: 10.4136/ambi-agua.170
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drainage status on soil and water chemistry, litter decomposition and soil respiration in central Amazonian forests on sandy soils

Abstract: Central Amazonian rainforest landscape supports a mosaic of tall terra firme rainforest and ecotone campinarana, riparian and campina forests, reflecting topography-induced variations in soil, nutrient and drainage conditions. Spatial and temporal variations in litter decomposition, soil and groundwater chemistry and soil CO 2 respiration were studied in forests on sandy soils, whereas drought sensitivity of poorly-drained valley soils was investigated in an artificial drainage experiment. Slightly changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Pacific et al (2008) showed that the soil CO 2 concentrations were significantly higher in the riparian zone as a result of higher soil moisture. In contrast, Zanchi et al (2011) found lower SR in plots after drainage, and suggested that the low C and N content in the topsoil near the river, where most of the soil CO 2 respiration is produced, could partially explain that low SR. The discrepancy of these two studies could be associated with the different drainage regimes as the poorly drained plots imply the anaerobic inhibition of SR.…”
Section: Effect Of Groundwater Level and Soil Moisture On Srmentioning
confidence: 46%
See 1 more Smart Citation
“…Pacific et al (2008) showed that the soil CO 2 concentrations were significantly higher in the riparian zone as a result of higher soil moisture. In contrast, Zanchi et al (2011) found lower SR in plots after drainage, and suggested that the low C and N content in the topsoil near the river, where most of the soil CO 2 respiration is produced, could partially explain that low SR. The discrepancy of these two studies could be associated with the different drainage regimes as the poorly drained plots imply the anaerobic inhibition of SR.…”
Section: Effect Of Groundwater Level and Soil Moisture On Srmentioning
confidence: 46%
“…Additionally, landscape position and topography not only altered the availability of soil water but also affected the annual range of soil moisture. This was shown in Zanchi et al (2011), studying riparian SR in Amazonia. They indicated that riparian soil is very sensitive to the changes of water-flooding regimes.…”
Section: Effect Of Groundwater Level and Soil Moisture On Srmentioning
confidence: 99%
“…This finding suggests that insect galls are favored in stressful environments, since slopes are comparatively the most stressful habitat within Amazonian terra firme forests. Slope habitats have the lowest levels of water and nutrients compared to the other habitats studied (Zanchi et al 2011). A study by Luizão et al (2004) indicated that slope and plateau habitats presentes higher nitrogen levels in their living leaves, litter and soil upper layer than that observed in the valleys, while carbon concentration in the vegetation samples did not vary among these habitats, therefore resulting in a high C:N ratio in valley habitat.…”
Section: Discussionmentioning
confidence: 99%
“…The water table is at greater depths in the plateaus, and approaches the surface towards the bottom of the valleys (Tomasella et al 2007;Zanchi et al 2011). Likewise, there is an increasing content of sand in the soil from plateau to valleys, with a corresponding decrease in clay content.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation